Bacterial-derived extracellular polysaccharides reduce antimicrobial susceptibility on biotic and abiotic surfaces. (October 2022) - Souza, Joāo Gabriel S.; Costa Oliveira, Bárbara E.; Costa, Raphael C.; Bechara, Karen; Cardoso-Filho, Otávio; Benso, Bruna; Shibli, Jamil Awad; Bertolini, Martinna; Barāo, Valentim A.R.
Abstract: Objective: Extracellular biofilm matrix plays a role in reducing bacterial susceptibility against antimicrobials. Since the surface where biofilm is growing modulates microbial accumulation and bacterial-derived exopolysaccharides (EPS) synthesis, this study compared the role of EPS to reduce antimicrobial susceptibility on biotic (dental surface) and abiotic (titanium (Ti) material) surfaces and the effect of remaining matrix-enriched biofilms to promote bacterial recolonization. Design: 48 h Streptococcus mutans UA159 strain biofilms were grown on enamel and Ti surfaces. The medium was supplemented with 1% sucrose, substrate for EPS synthesis, or with 0.5% glucose + 0.5% fructose as control. Chlorhexidine (CHX) 0.2% was used for antimicrobial treatment. Biofilms were collected and the following analyses were considered: viable bacterial counts, biofilm pH, EPS content, and biofilm structure by scanning electron microscopy and confocal laser scanning microscopy (CLSM). Substrate surfaces were analyzed by 3D laser scanning confocal microscope. Results: Enamel surface showed a higher amount of EPS content (p < 0.05), which may be explained by the higher bacterial biomass compared to Ti material. EPS content reduced bacterial susceptibility against antimicrobial treatments for both substrates, compared to EPS control (p < 0.05). However, sucrose-treated cells presented the same magnitude of reduction for Ti or enamel. Interestingly, matrix-enriched biofilms favored bacterial recolonization for both substrates. Conclusion: The surface where the biofilm is growing modulates the amount of EPS synthesized and matrix content plays a key role in reducing antimicrobial susceptibility and promoting bacterial recolonization. Highlights: Biofilm matrix reduces microbial susceptibility against antimicrobials. Surface properties modulates microbial adhesion and accumulation. Biofilm matrix reduced antimicrobial effect on dental and titanium surfaces. Matrix-enriched biofilms favored bacterial recolonization for both substrates.